Il sesso inutile (1961) d’Oriana Fallaci : aux origines de l’islamophobie d’une icône italienne - Iz Séverin (Cahiers d’histoire)
Il sesso inutile. Viaggio intorno alla donna (1961) (« Useless Sex. A Journey Around the Woman ») is the first text published by Oriana Fallaci and has been somewhat forgotten by critics in favour of her later production. It is, however, a fundamental text for understanding that the author's hatred of Islam arose long before its official birth, proclaimed in a very functional and opportunistic way by the media and politicians as dating from the attacks of 11 September 2001. This article therefore proposes to go back to this first writing and to show that a form of Islamophobia is already present, as well as racist and colonialist components, and the presence of a right-wing feminism. Given the media mobilisation of Oriana Fallaci in Italy, this text also allows us to question the strengths and possibilities of a cultural, social and political anti-racism in the face of the prominence of such a figure in the imaginary and in current nationalist discourses.